Immunotherapy biomarkers in brain metastases: insights into tumor microenvironment dynamics - Li, Mu; Zhang, Yi; Yu, Duo; Yu, Yaoyu; Ma, Wenxue (Frontiers in Immunology, 2025)
Brain metastases (BM), represent the most common intracranial malignancies in adults and remain a major clinical challenge due to their poor prognosis and limited therapeutic options. Although immunotherapy has emerged and offers a promising strategy, its efficacy in BM is often compromised by the immunosuppressive tumor microenvironment (TME) and limited immune cell infiltration. This review highlights the critical role of cytokines and growth factors as key modulators of immune dynamics in the TME, exploring their utility as predictive and prognostic biomarkers for immune response. We examine selected categories of biomarkers including genomic, proteomic, immunological, circulating, and microenvironmental, specifically through the lens of cytokine and growth factor regulation. Additionally, we highlight how advanced technologies, including next-generation sequencing (NGS), single-cell RNA sequencing (scRNA-seq), spatial transcriptomics, and liquid biopsies, contribute to the identification and validation of these biomarkers. By addressing current challenges and proposing future directions, this review underscores the translational value of cytokine- and growth factor-related biomarkers in optimizing precision immunotherapy for patient s with BM.